PEMANFAATAN RUMPUT LAUT Sargassum sp. DALAM BENTUK PAKAN KONSENTRAT UNTUK MEMPERBAIKI PERTAMBAHAN BERAT BADAN PADA KAMBING - Nurbaya, Nurbaya; Kiramang, Khaerani; astati, astati (Teknosains: Media Informasi Sains dan Teknologi, 2018)
This study aims to determine the effect of seaweed Sargassum sp. To weight gain in goats. Concentrate feeding using a different treatment is feed with the addition of Sargassum sp. 10% and 15% and without the addition of Sargassum sp. Research method used Completely Randomized Design (RAL) with 3 treatments and 5 replications ie P0 5 female goat (Control), P1 5 female goat + seaweed Sargassum sp. 10%, P2 5 female goat + seaweed Sargassum sp. 15%. To know the weight gain daily (PBBH). Weighing every 10 days for 2 months. The results showed that average weight gain P0 control 0.014 kg / head / day, P1 (Sargassum sp. 10%) 0.052 kg / day / tail, P2 (Sargassum sp.15%) 0.066 kg/day/The provision of Sargassum sp. had no significant effect on the daily weight gain of female goats, but the graph shows that there is a tendency of daily weight gain of female goats in each treatment